PRIMER REGISTRO PARA EL CARIBE COLOMBIANO DE PORPITA PORPITA (LINNAEUS) (HYDROZOA: PORPITIDAE) (Boletín de Investigaciones Marinas y Costeras, 2016)
Two specimens of Porpita porpita were captured in Playa Blanca, Gaira Bay and the species reported for the fist time in the Colombian Caribbean. This paper collects bibliographic information about blue button (Hydrozoa: Porpitidae) hydroid colony.